HUBUNGAN SIKAP DENGAN KINERJA KADER POSYANDU Studi Observasional Analitik Kader Posyandu di Wilayah Puskesmas Bangetayu Semarang - Safira Yuliana; Purwito Soegeng Prasetijono (PT. Hasba Edukasi Mandiri, 2026)
Posyandu is a community-based health service whose success is highly influenced by the participation and performance of cadres. Cadres’ attitudes, which include cognitive, affective, and conative aspects, play a role in determining the quality of Posyandu activity implementation. A problem that is still found is the variation in cadres’ attitudes and performance; therefore, research is needed to analyze the relationship between attitude and the performance of Posyandu cadres in the working area of Bangetayu Primary Health Center, Semarang. This study was an analytic observational study with a cross-sectional design involving 76 Posyandu cadres. Data were collected using attitude and performance questionnaires that had been tested for validity and reliability. Data analysis was conducted using univariate analysis to determine the frequency distribution of variables and bivariate analysis using the Spearman correlation test. The results showed that most cadres’ attitudes were in the good and fair categories (48.7% each), while cadre performance consisted of very good (34.2%), good (34.2%), and fair (31.6%) categories. The Spearman test indicated a significant relationship between attitude and cadre performance (p < 0.001) with a moderate strength and positive direction (r = 0.372). It can be concluded that cadres’ attitudes influence the performance of Posyandu cadres, and better attitudes are associated with better cadre performance.